Physiological responses associated with cardiopulmonary exercise testing in elite football referees, distance runners and health controls - Silva, Vitor Loureira da (2021)
The aerobic physical fitness levels of soccer referees is of great interest, because its can impact on the quality of the referees' performance during matches. This study evaluated the physiological response from aerobic physical fitness variables [maximal oxygen uptake (VO2max), anaerobic threshold (AT) and respiratory compensation point (RCP)] obtained from the cardiopulmonary exercise test (CPET) in soccer referees and compare it to those of healthy controls and distance runners. A cross-sectional study was performed with 57 male adults that composed the following groups: control group (CG); recreational runners (RuG); and soccer referees (ReG). Anthropometric, resting and exertion electrocardiograms and CPET evaluations were determined. Brazilian elite soccer referees have a higher speed and VO2max associated with AT, RCP and maximal exercise (CG=39.8±4.7 versus RuG=52.4±7.1; and ReG=45.8±5.5 ml/kg/min), than CG, but lower than the recreational runners. Physiological responses associated with the CPET of Brazilian elite soccer referees are higher than those of healthy controls, but lower than those of recreational runners. From our results and other findings in the literature, we can assume, that the soccer referees evaluated are able to withstand the physiological demands imposed by the match.